John Franklin (1786-1847) - Davis, Richard C. (ARCTIC, 1985)
. The man who charted nearly 3000 km of the coastline of North America is best remembered as the leader of an expedition that cost the British Admiralty two ships and the lives of 129 men and that made no direct contribution to the geographical unfolding of the Canadian Arctic. . Franklin endured an enforced idleness for three years before he was put in command of the brig Trent, which was to accompany the Dorothea under David Buchan up the east coast of Greenland and, it was hoped, over the Pole to the Orient. The voyage came to naught, the ships being turned back by heavy ice near Spitzbergen. In the same year, 1818, John Ross had been sent on an ancillary expedition to look for an opening leading out of Baffin Bay; when Ross returned to England to report that Baffin Bay offered no westward egress, John Barrow, Secretary to the Admiralty, refused to believe him. Hence, in 1819 the Admiralty dispatched Edward Parry to search Baffin Bay again, while Franklin went across the mainland to explore the northern cost east of the Coppermine River's mouth. . The advanced season and a mutinous crew forced him back at Point Turnagain on Kent Peninsula. To avoid the treacherous return along the coast in the much-weakened bark canoes, Franklin decided upon a 500 km overland crossing by compass-bearing to Fort Enterprise, a journey that took them across the Barrens and that witnessed the deaths by starvation and exposure of nearly half the party of 20, at least one murder, an execution without trial, and suspected cannibalism. Franklin and two of his three officers survived; the voyageurs paid the heaviest toll, only 2 out of 11 returning. . With a well-disciplined crew of 27, comprising mostly British seamen and marines and including Dr. John Richardson and George Back, survivors of the 1819-1822 expedition, Franklin set off for Great Bear Lake [in 1825]. There the party built Fort Franklin, a winter residence near the Great Bear River, which drains the lake into the Mackenzie River. After wintering at Fort Franklin, they ...